A systematic video analysis of National Hockey League (NHL) concussions, part II: how concussions occur in the NHL. Issue 8 (1st May 2013) - Hutchison, Michael G; Comper, Paul; Meeuwisse, Willem H; Echemendia, Ruben J
Abstract : Background: Concussions in sports are a growing cause of concern, as these injuries can have debilitating short-term effects and little is known about the potential long-term consequences. This work aims to describe how concussions occur in the National Hockey League. Methods: Case series of medically diagnosed concussions for regular season games over a 3.5-year period during the 2006–2010 seasons. Digital video records were coded and analysed using a standardised protocol. Results: 88% (n=174/197) of concussions involved player-to-opponent contact. 16 diagnosed concussions were a result of fighting. Of the 158 concussions that involved player-to-opponent body contact, the most common mechanisms were direct contact to the head initiated by the shoulder 42% of the time (n=66/158), by the elbow 15% (n=24/158) and by gloves in 5% of cases (n=8/158). When the results of anatomical location are combined with initial contact, almost half of these events (n=74/158) were classified as direct contact to the lateral aspect of the head. Conclusions: The predominant mechanism of concussion was consistently characterised by player-to-opponent contact, typically directed to the head by the shoulder, elbow or gloves. Also, several important characteristics were apparent: (1) contact was often to the lateral aspect of the head; (2) the player who suffered a concussion was often not in possession of the puck and (3) no penalty was called on the play.